2021
DOI: 10.3390/biology10121333
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Fluoroscopy Cardiac Ablation: Technology Is Moving Forward in Complex Procedures—A Novel Workflow for Atrial Fibrillation

Abstract: Background and Rationale. A fluoroscopy-based approach to an electrophysiological procedure is widely validated and has been recognized as the gold standard for a long time. The use of fluoroscopy exposes both the healthcare staff and the patient to a non-negligible dose of radiation. To minimize the risks associated with the use of fluoroscopy, it would be reasonable to perform ablation procedures with zero fluoroscopy. This approach is widely used in simple ablation procedures, but not in complex procedures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In addition, the formation of microbubbles, visible with ICE, may be a frequent indication of excessive heating of the tissues during radiofrequency delivery and, finally, to select in certain cases the site of puncture of the oval fossa in relation to the type of procedure, with the possible benefit of the maneuverability of catheters [ 17 ]. Finally, the integration of the ICE with electroanatomical mapping systems has also proved very promising in the drastic reduction in scan times during TSC [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the formation of microbubbles, visible with ICE, may be a frequent indication of excessive heating of the tissues during radiofrequency delivery and, finally, to select in certain cases the site of puncture of the oval fossa in relation to the type of procedure, with the possible benefit of the maneuverability of catheters [ 17 ]. Finally, the integration of the ICE with electroanatomical mapping systems has also proved very promising in the drastic reduction in scan times during TSC [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Consequently, fluoroless or near-fluoroless radiofrequency (RF) CA for AF has been enabled using a three-dimensional (3D) electroanatomical mapping system, transoesophageal echocardiography (TEE), or intracardiac echocardiography (ICE). 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Complete ZF approach for complicated arrhythmias such as atrial fibrillation and VAs originating from the left ventricle normally requires a combination of the 3D EAM system and intracardiac echocardiography (ICE), which ensures the safety of atrial septal puncture, as well as good catheter‐tissue contact. 8 , 9 However, ablation of less complex arrhythmias, such as VAs originated from right side of the heart, with the guidance of 3D EAM, can be performed with complete ZF without ICE assistance. 10 , 11 The results of recent studies have shown that ZF ablations under the guidance of a 3D EAM system for patients with idiopathic right‐sided VAs are safe and feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Zero‐fluoroscopy (ZF) ablations using 3D electroanatomical mapping (EAM) system for various types of arrhythmias has emerged as an effective alternative and is being performed in many centers worldwide, 6,7 but rarely done in Vietnam. Complete ZF approach for complicated arrhythmias such as atrial fibrillation and VAs originating from the left ventricle normally requires a combination of the 3D EAM system and intracardiac echocardiography (ICE), which ensures the safety of atrial septal puncture, as well as good catheter‐tissue contact 8,9 . However, ablation of less complex arrhythmias, such as VAs originated from right side of the heart, with the guidance of 3D EAM, can be performed with complete ZF without ICE assistance 10,11 .…”
Section: Introductionmentioning
confidence: 99%